(untitled) (Medico Legal Update, 2019)
Background: There are considerable hypothesis about possible relationship between panic disorder (pd) and mitral valve prolapse (MVP), panic disorder usually consider as impact factor on patient with (MVP) either in exaggeration of symptoms or complications of (MVP) like angina, chest pain, chronicity of course of (pd). (MVP) is myxotamous disconfiguration of valve due thickening and dislocation of valve leaflet into left atrium through systole. Patients and Method: Cross sectional study of (52) patients with panic disorder with MVP (31) or without (21) through the period (March- October 2018) in private clinics of (physician, psychiatrist, Echocardiographic specialist), all study sample were submitted to (DSMIV) criteria to document panic disorder diagnosis by psychiatrist and physical assessment. Results: All study sample (52) patients were documented as (pd), (31) patients (59.6%) were with negative (MVP), 21 patients (40.4%) were with positive, < 20 year age group were the major with positive MVP, >60 year were the major negative (MVP) their percentage were (66.7%,100.%) successively, most common count of positive (MVP) who were unemployed were (44.4%) in comparism with (55. 6%) with negative (MVP), (41. 2%) of MVP were from rural area, (60. 0%) were with negative MVP,(50. 0%) of positive Mitral valve were from moderate social class, which is equal to negative (MVP) (46. 2%),